2021
DOI: 10.1007/s13204-021-02087-w
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profile and larvicidal activity of aqueous extract of Ocimum americanum against mosquito vectors

Abstract: The primary goal of this research was to evaluate the phytochemicals, including bioactive components of Ocimum americanum extracts and assess their larvicidal potential against 3rd and 4th instar larvae of Aedes aegypti, Anopheles stephensi, and Culex quinquefasciatus. The aqueous extraction process on O. americanum provides higher yield (9.61 ± 0.11%) and a significant volume of phytochemicals (tannins, saponins, terpenoids, flavonoids, alkaloids, protein, and carbohydrate) than other solvents (methanol, etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…78,79 Primary metabolites such as protein, amino acid, carbohydrate, fatty acid, and minerals are among the nutritional elements found in Ocimum americanum plants that are good for human health. 80,81 According to Mustafa and El-kamali 82 calcium content, iron content, salt content, potassium content, manganese content, and zinc content were detected in significant amounts in the elemental analysis of Ocimum americanum plant leaf and flower conducted using atomic absorption spectroscopy and flame emission techniques (Table 3).…”
Section: General Information and Structural Profile Of Ocimum Americanummentioning
confidence: 99%
“…78,79 Primary metabolites such as protein, amino acid, carbohydrate, fatty acid, and minerals are among the nutritional elements found in Ocimum americanum plants that are good for human health. 80,81 According to Mustafa and El-kamali 82 calcium content, iron content, salt content, potassium content, manganese content, and zinc content were detected in significant amounts in the elemental analysis of Ocimum americanum plant leaf and flower conducted using atomic absorption spectroscopy and flame emission techniques (Table 3).…”
Section: General Information and Structural Profile Of Ocimum Americanummentioning
confidence: 99%
“…Unlike the more pronounced members of the Ocimum genus, for instance, O. basilicum , O. sanctum , and O. tenuiflorum , which are immensely investigated for their mosquitocidal and repellency properties, there is minimal research and evidence to reflect on the larvicidal efficacy of the extracts and essential oils of O. americanum against mosquito vectors. Only recently, Narayanan et al [ 49 ] reported on the bioactive components of the aqueous extracts of O. americanum, which showed significant larvicidal properties against Ae. aegypti , An.…”
Section: Introductionmentioning
confidence: 99%
“…Although medicinal plant extracts possess excellent potential for treating bacterial infections caused by drugs resistant pathogens. It is interesting to know that >5% of the world's plant species have indeed been studied as potential medicines thus far, with the remaining 95% still yet to be studied [8][9][10]. Interestingly, the phytochemicals from the plant extract also have the potential to synthesize the nanoparticles with pharmaceutically valuable, therapeutics [3,11].…”
Section: Introductionmentioning
confidence: 99%